Baby leafs biofortificadas com lítio : desenvolvimento, efeito neuroprotetor e características bioquímicas das plantas - Martins, Rafael Alexandre dos Santos (2023)
The objective of this study was to evaluate the impact of the root application of lithium carbonate (Li2Co3) on the productivity and on the nutritional and bioactive characteristics of four brassica cultivars: Arugula, Cabbage, Red Cabbage and Mustard. Root biofortification was performed with lithium carbonate at concentrations of 0, 15, 30, 60 and 120 mg. L-1 for 15 days. Then, weight, height of plants, number of plants and number of leaves were evaluated. Additionally, the plants were evaluated for total phenolic compounds content, antioxidant capacity measured by DPPH, ABTS and FRAP methods, mineral profile and amount of lithium absorbed. Among the doses tested, the dose of 60 mg. L-1 showed greater growth stimulation for arugula, resulting in the ability to maintain plant weight statistically equal to the control group. As for the levels of total phenolic compounds and antioxidant activity, the highest values were obtained at the Li concentration of 60 mg. L-1, with a significant difference compared to the control group. Lithium assimilation capacity varied proportionally according to the offered dose, demonstrating a dose-dependent behavior. The results obtained in the present study demonstrated that, under the analyzed conditions, there are benefits from the application of Li in doses of 30 mg. L-1 and 60 mg. L-1 proven by the improvement of productivity and nutritional and bioactive properties of the studied species. It was also possible to observe that arugula extracts resulted in beneficial effects on the development of Drosophila Melanogaster, in the pupal stage and there was also a beneficial effect on the survival rate and climbing ability of the animals.